FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI OPERATOR PRODUKSI TERHADAP RESIKO BAHAYA TIMBAL DI INDUSTRI MANUFAKTUR LEAD ACID STORAGE BATTERY - Daniel Sembiring; Sahat Sinambela (LPPM, 2011)
Usage of dangerous Materials in inseparable industry so that negative impact of risk to health of worker which in it become important attention. From breakdown of background above, hence problem of research shall be as follows : many operator which still disregard lead danger risk and also by dozens operator which do not know lead danger to environment. Target to know factors influencing operator perception produce to lead danger risk in battery storage acid lead manufaktur industry and to know dominant factor from factors influencing operator perception to lead danger risk. This research pass/through formulation of problem of, determining target, book study, research method desain, data collecting in the form of matrik so that easy to in data input, data-processing with SPSS release 17 and hereinafter conclude. From result of research can be concluded that factors having an effect on direct to worker perception to lead danger risk [is] ( 1) control systems operation of lead danger. ( 2) interaction with lead danger. ( 3) factor training of K3. ( 4) Climate K3 in company organization also give influence to worker perception. Suggested to increase control systems operation of lead danger and also training system mereview so that/ to be worker perception become attitude and goodness posed at in working to fulfill healthy and peaceful job/activity standard Keywords: